The influence of smartphone colour palettes on consumers’ attitudes and purchase intentions - Maier, Alissa; Karlíček, Miroslav, 1979-; Keprta, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
Despite its importance, the concept of colour is not widely understood in marketing. This thesis establishes conventionally, and unconventionally coloured smartphone lines based on desk research. The influence of these smartphone colour palettes on consumers’s attitudes to the visual appeal of the product line, the brand personality with regards to originality, the brand itself, and purchase intention were then researched. Four hypotheses were tested on a sample of 101 subjects. The results demonstrated that smartphone colour palettes have significant impacts on consumers’ attitudes and on their purchase intentions. Finally, colour strategies for incumbent and new market players based on the results are presented.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses